Treatment of Municipal Wastewater through Constructed Wetland - Anwar Tahseen; Singh Bihari; Kumar Rakesh (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Constructed wetlands are artificial wastewater treatment system of shallow experimental tanks, ponds or channels that are planted with locally available wetland plants. They work on natural capacity of plants to treat wastewater from different sources. In view of rising concern about pollution of water bodies due to discharge of waste in them, it is necessary to initiate alternative thinking as conventional methods through STPs (Sewage treatment Plants) have had limited success. In recent years the application of specifically designed wetland based technology (popularly known as Phytorid technology) for treatment of wastewater- municipal, urban and agricultural, is becoming widely acceptable. The technology has been found to be very effective in water pollution control as it functions as water ‘pollutant sinks’ for sediments, nutrients and metals. It treats the wastewater in natural manner without the use of chemicals. In short, Phytorid technology is an improved wetland system for treatment of wastewater. The present research work was undertaken by our team on a constructed wetland designed and developed at A. N. College, Patna which is location specific. It has locally available wetland plants which are economically and spatially feasible for wetland study in and around Patna, the capital city of Bihar (India) and for those regions of state which have similar climatic conditions. The main objective of present research work is to provide and popularize a simple, feasible, practically sound, ecofriendly and cost effective technology for wastewater treatment and its reuse in the state of Bihar (India).